Capital Structure Choice and Company Taxation: A Meta-Study - Lars P. Feld; Jost Henrich Heckemeyer; Michael Overesch (Verein für Socialpolitik, 2010)
This paper provides a quantitative review of the empirical evidence on the impact of taxation on corporate debt finance. On the basis of 626 primary estimates taken from 23 studies, we find that the median tax-rate elasticity of debt ratios is around 0.44. The median tax-rate elasticity of incremental debt changes amounts to 2.47. There is, however, considerable variation in estimated tax effects on financial leverage. By means of meta-regressions, the paper aims to systematically explain this variation in terms of underlying study characteristics. The meta-regressions indicate that the heterogeneity in the semi-elasticities from the different studies can be fairly well explained by the characteristics of these studies. We find that the estimated tax elasticities are more pronounced if large firms or holding companies are considered. Moreover, our results suggest significantly higher tax elasticities of intercompany debt supporting the view that tax planning strategies of multinational firms affect debt financing.
Keywords: G30; H32; F23; 330; Capital Structure; Corporate Income Tax; Tax-Elasticity; Meta-Analysis